2020
DOI: 10.7888/juoeh.42.261
|View full text |Cite
|
Sign up to set email alerts
|

Pembrolizumab-induced Radiation Recall Pneumonitis After the Resolution of Typical Asymptomatic Radiation Pneumonitis

Abstract: Radiation recall pneumonitis is a phenomenon in which a recall-triggering drug induces an acute inflammatory reaction in the lungs, corresponding to a previously irradiated area. Radiation recall reactions have been reported to occur following treatments with various cytotoxic anticancer agents and molecular-targeting drugs; however, only a few reports have described immune checkpoint inhibitor-induced radiation recall pneumonitis. We report a case of radiation recall pneumonitis induced by pembrolizumab in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Possible mechanisms of this type of pneumonia include stem cell function changes in the irradiated field triggered by hypersensitivity reactions to an idiosyncratic drug (119). Some case reports have presented radiation recall pneumonia in patients with NSCLC after treatment with ICIs (60,85). Patients who receive RT and develop new pulmonary changes demarcated from the adjacent lung in the initial radiation field should be preferentially suspected of having radiation recall pneumonia.…”
Section: Imaging Manifestationsmentioning
confidence: 99%
“…Possible mechanisms of this type of pneumonia include stem cell function changes in the irradiated field triggered by hypersensitivity reactions to an idiosyncratic drug (119). Some case reports have presented radiation recall pneumonia in patients with NSCLC after treatment with ICIs (60,85). Patients who receive RT and develop new pulmonary changes demarcated from the adjacent lung in the initial radiation field should be preferentially suspected of having radiation recall pneumonia.…”
Section: Imaging Manifestationsmentioning
confidence: 99%
“…After the resolution of radiation-induced pneumonitis, radiation recall pneumonitis, an acute inflammatory reaction in a previously irradiated area of the lung triggered by other anticancer drugs can occur (40). In a case report by Itamura et al, the patient developed radiation recall pneumonitis one month after initiating pembrolizumab, who had previously recovered from radiation pneumonitis (41).…”
Section: Radiotherapymentioning
confidence: 99%
“…In the MDACC study, two patients with simultaneous HFRT or SBRT combined with PD-1 inhibitor had Grade 4 adverse effects, which may be attributed to the simultaneous medication. A study by ESMO 2020 showed that the administration of anti-PD-1 drugs before or during radiotherapy for thoracic tumours increased the incidence of radiation pneumonitis (60% 28%, P = 0.01) compared with the administration of anti-PD-1 drugs after radiotherapy ( 55 , 56 ). However, the occurrence of adverse effects is closely related to factors such as radiotherapy dose, volume and location.…”
Section: Efficacy Of Different Combinations Of Radiotherapy and Pd-1/pd-l1mentioning
confidence: 99%